The Treaty of Good Neighbourship and Friendly Cooperation of 17 June 1991 between the Republic of Poland and the Federal Republic of Germany: Origin, Aims and Implementation. Successes, Failures and Prospects in the Context of the Migration Crisis in Euro (Economic and Political Thought, 2018)
The aim of the article is to present the origin of the Polish-German Treatyof Good Neighbourship and Friendly Cooperation of 17 June 1991 and itssignificance for the process of reconciliation and development of versatilecooperation between Poland and Germany in the context of the presentmigration crisis in Europe. The author formulates a few interesting thesesand tries to answer many questions concerning Polish-German relations inthe period 1989–2018 and their conditions and prospects. Over the last twoyears, Polish-German relations, especially political ones, have considerablydeteriorated. The international situation in Europe has also become morecomplicated. One of the reasons of the situation is the immigration crisisresulting from a massive influx of people from the Middle East and NorthAfrica. The immigration crisis has divided the European Union and hasaffected relations between its Member States, including Polish-Germanrelations.
Keywords: Treaties, Poland, Germany, reconciliation, cooperation